LITERASI INKLUSIF DALAM PENGEMBANGAN KEMAMPUAN BERBAHASA MAHASISWA DISLEKSIA DI PERGURUAN TINGGI - Eni Nurhayati; M. Ludfy Hadis Maqfiro; Dewi Andriani; Esa Amirotus Sholichah (Balai Bahasa Provinsi Bali, 2025)
This study examines inclusive literacy practices in supporting the language abilities of university students with dyslexia. The research is grounded in the presence of linguistic barriers that affect academic text comprehension and equal access to learning. Employing a qualitative approach with a phenomenological case study design, data were collected through in-depth interviews, participatory observations, documentation, and supported by descriptive questionnaire results. Data were thematically analyzed using the Miles and Huberman model. The findings reveal that difficulties in understanding academic readings constitute the most prominent linguistic challenge experienced by students with dyslexia. Questionnaire data are used descriptively to strengthen qualitative interpretations, indicating that most participants perceive this challenge consistently. Furthermore, inclusive learning support strategies particularly the provision of audio-visual materials and flexible assessment methods are perceived as highly effective in facilitating learning participation. These findings affirm that linguistic barriers can be reduced through adaptive learning approaches and inclusive educational policies, enabling students with dyslexia to engage more optimally in academic processes.